A hibridação presente na música cristã terena da aldeia Aldeinha - Schneider, Isabel Cristina Blum (2018)
The object of study of this research is the Terena Christian indigenous music (hymns and psalms), inserted in the Lutheran’s rituals that take place in the Evangelical Lutheran Congregation from Anastácio and at the Bible studies at Igreoca – church in hollow shape, constructed in de Aldeinha village, Anastácio, Mato Grosso do Sul. This village, of Terena ethnicity, suffered transformations in its culture due to constant missionary’s visits, among other factors, as the deterritorialization and urbanization. It was observed certain Terena and Lutheran cultural hybridization, besides other ethnic and denominational interculturalities in the style of the music intoned by the Lu-Terena choir – a choir of the local Igreja Evangélica Luterana do Brasil, formed by Terena indigenous from Aldeinha. The goal of this research is to identify the Christian music hybridization present in the village Aldeinha songs in the source language Aruák, seeking to understand the interrelation of cultures that happens between Lutherans and Terenas across the music of Protestant Christian from the villagers that attend the Igreoca and to point out peculiarities existed in this process, as well as to verify if there are the appreciation of the Terena culture in this practice. Various methods of analysis have proved to be necessary in order to help in the results of a westernized style of music sung by an indigenous ethnicity: historical-sociological; traditional (stylistic, structural and functional); anthropological, musicological and ethnomusicological. Regarding the methodology addressed for the research data collect and the writing of this paper, its study design was observational. The character was qualitative. The unit of analysis was the Terena Christian music sung in Aruák language. The multifocal resources used for the data collects, in loco, were: the writing of a logbook, interviews, audio and video recordings, bibliographic and documental researches. The search results demonstrated how occurs the cultural exchanges between Lutherans and Terena, which are part of this context.